Evaluasi Usability Aplikasi Digital Citizen Journalist Dengan Menggunakan Metode Usability Testing - Adelia Ayu Trilestari; Hanifah Muslimah Az-Zahra; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Digital Citizen Journalist (DJ) is a mobile application to write reviews owned by Times Indonesia. This application is made with intention to fulfill public needs and make it easier for them to convey their aspirations. This application needed an usability evaluation to help its users to use it. Usability component tested in this study are learnability, efficiency, memorability, error and satisfaction. This research use usability testing method, interview and system usability scale questionnaire (SUS). All of the participant in this research are DJ's new user with age range between 15-17 years old, 18-24 years old and 25-64 years old. Usability testing and interview conducted with nine participant in order to find out about its learnability, efficiency, memorability and error component and also its problems. SUS questionnaire filled by 20 participant to find out about its satisfaction component. The evaluation results shows efficiency (0,12 goals/sec and 74%), errors (0,29), increased memorability, satisfaction (74) and good learnability. This results indicates needs for further research. From interviewing participants found 40 problems with 20 different problems. From all problems found, 17 recommendations about application interface and application features are given based on suitable guidelines. These recommendations are also given with all the age categories in mind to give the optimal solution.